Integrasi Ilmu dalam Perspektif Hasan Asari - Diah Rahmawati; Danny Abrianto; Ismaraidha (Medan Resource Center, 2025)
The purpose of this study was to determine: 1) The nature of science in Hasan Asari's perspective, 2) The concept of ontology, epistemology, and axiology of science in Hasan Asari's perspective, and 3) The concept of integration of science in Hasan Asari's perspective. This research uses a character study research method. The data sources in this research are direct interviews with figures, and supported by books, articles or journals. The findings of the study indicate that, according to Hasan Asari’s perspective: 1) science refers to knowledge whose validity has been verified; 2) the ontology of science centers on Allah as the ultimate reality, while its epistemology encompasses bayani, burhani, tajribi, and ‘irfani approaches; and its axiology emphasizes that scientists must prossess a strong moral orientation; 3) the concept of integration of science from the cause of the dichotomy of science and educational institutions becomes the foundation.